KOMPOSISI DAN STRUKTUR GASTROPODA DI SUNGAI KUANTAN DESA LUBUK TERENTANG KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI, RIAU - Utami, Heffy; Nurdin, Jabang; Lusi, Armen (STKIP PGRI Sumbar, 2013)
ABSTRACT The Gastropod is macroorganism in the water. It is important for live organism in the water, it is as primary consumer. The research purpose to know the composition and structure of the Gastropod in the Kuantan river. The research was carried out in may of 2013 with a descriptive survey method in purposive random sampling with a set of field conditions based on station. This method is used because there are MCK, gold minning, rubber plantation. A total of Gastropod species found are 14 species belong 9 genera, 4 families and 1 ordo. Thiaridae found as the families with the highest of species (7 species), followed by Pleuroceridae (5 species), Pachychilidae and Cochlipidae found 1 species. Melanoides anomala found as dominant species (18,34%). The highest of totally density showed in the station II (22,37 individu/m2) and the lowest density showed in the station III (16,00 individu/m2). Indeks diversity of Gastropod in the Kuantan river turn 1,39-2,14, So the Kuantan river into medium pollution category. Physics and chemistry factor in the Kuantan river suitable to life the Gastropod.